ANTHROPOLOGICAL PROJECT AS A BASIS OF CARTESIAN ETH-ICS - A. M. Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is to determine and understand the conditions of the anthropological project development by Descartes. It implies the necessity to conceive its entrenched forms in scientific revolution, which leads to a) a human as an embodiment of some abstract mind, b) its transcendence, as well as the possibility to penetrate into a human nature in the course of ethics development. Originality. According to the author, the anthropological interpretation of Descartes is not profound, since a human is taken as embodiment of abstract mind, and ethics is a set of some simple rules. The impact of scientific revolution, which was not well perceived, leads to the domination of a restricted understanding of a human in research literature. The author insists on taking into account the fact that Descartes was beyond epistemology due to the topical issue concerning a proper mode of life. Conclusions. The incomprehensive interpretation of the attitude of Descartes to scientific revolution causes restricted understanding a human nature as abstract mind embodiment and ethics as a set of simple rules. Thorough analysis of the thinker's texts proves his profound interpretation of scientific revolution impact and integrated vision of a human nature, as well as significant development of ethical issues.